Between idealism and realism: a comparative analysis of the reparations regimes of the International Criminal Court and the Extraordinary Chambers in the Courts of Cambodia - Letschert, Rianne (International journal of comparative and applied criminal justice, 2021)
This article investigates the approach to reparations of the International Criminal Court (ICC) and the Extraordinary Chambers in the Courts of Cambodia (ECCC), using a comparative law perspective, complemented by socio-legal insights. We trace back the development of the reparative frameworks of the ICC and ECCC, and identify the normative bases and political climate underlying the establishment of both courts. Moreover, we scrutinize their case law and implementation practice on reparations, and posit that the initial context of development will not predict how well the courts will fare in practice. Instead, we argue that the openness and flexibility of the courts, to acknowledge when change is needed and adapt to challenges arising during the process of designing and implementing reparations appear to be more important than the initial context. We conclude that in order to make the victims’ right to reparation real, the courts’ reparative mandates require a deeper reflection on the feasibility of the underlying goals of international criminal justice and a realistic assessment of their performance in practice.